1987
DOI: 10.1152/ajpgi.1987.252.4.g491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromedin B and neuromedin C on exocrine and endocrine rat pancreas

Abstract: Neuromedin B and neuromedin C are novel decapeptides that have recently been isolated from porcine spinal cord and canine intestinal mucosa and show striking sequence homology with bombesin and gastrin-releasing peptide (GRP-27) at the carboxyl-terminal region. The effects of synthetic neuromedin B and C on exocrine pancreatic function and insulin release have been compared with bombesin and GRP-27 in isolated pancreatic acini and isolated perfused pancreas in rat. Neuromedin B and C as well as bombesin and GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
4
16
1
1
Order By: Relevance
“…The results of the present investigation confirm the powerful stimulatory effect of both caerulein and bombesin on exocrine pancreatic secretion, already pointed out in different in vitro (Bertaccini, 1976;Gardner & Jensen, 1981;Jensen et al, 1984;Otsuki et al, 1987) and in vivo (Bertaccini, 1976;Namba et al, 1986;Varga et al, 1988a,b) experimental conditions. In our in vitro system, which was used for the first time to assess the pancreatic secretory action of these peptides, caerulein proved to be of equal efficacy compared to bombesin.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present investigation confirm the powerful stimulatory effect of both caerulein and bombesin on exocrine pancreatic secretion, already pointed out in different in vitro (Bertaccini, 1976;Gardner & Jensen, 1981;Jensen et al, 1984;Otsuki et al, 1987) and in vivo (Bertaccini, 1976;Namba et al, 1986;Varga et al, 1988a,b) experimental conditions. In our in vitro system, which was used for the first time to assess the pancreatic secretory action of these peptides, caerulein proved to be of equal efficacy compared to bombesin.…”
Section: Discussionsupporting
confidence: 91%
“…Its potency, however, was one order of magnitude higher than that of bombesin. This potency ratio was comparable to that found in rat (Otsuki et al, 1987) and guinea-pig (Gardner & Jensen, 1981) pancreatic acini. The results obtained with lorglumide demonstrate that this compound is a potent and selective antagonist of CCK-induced amylase release.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Concerning pancreatic hormone release, our recent in vivo and in vitro studies have demonstrated that NMB and GRP-10 clearly stimulate insulin release in dogs and that glucagon release was slightly stimulated by higher doses of GRP-10 and not by NMB (Kawai et al, 1988). On the other hand, in isolated perfused rat pancreases the stimulatory effect of NMB and GRP-10 on insulin release was not clear (Otsuki et al, 1987) in contrast to our results with isolated canine pancreas perfusion. Our previous study demonstrated that substance P stimulated insulin release from the isolated perfused canine pancreas and inhibited it from the rat pancreas (Chiba et al, 1985).…”
contrasting
confidence: 99%